A skin that took them through - Kgame, Mbali (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2020)
This project comprises of interlinked fictional short stories capturing experiences of the "invisibilised'' young people- the street kids, drug addicts, cashiers, childminders, the sick, first graduates etc. These stories are a way to interrogate the fallacy of a "free and fair" South Africa by noting events taking place within homes, communities and countrywide. Told in a playful, innocent, curious, childlike voice and reasoning, my work draws inspiration from Werewere Likings 'The Amputated Memory,' for its ability to narrate the current without divorcing the past. I draw inspiration from Liking's way of writing family connectivity and employing an emerging voice of the narrator starting from being a child scribbling to later becoming an elder. Nana Kwame Adjei-Brenyah's 'Black Friday' for scanning into young black people's experiences in a society where their bodies move as misfits. My work also draws from Lesley Nneka Arimah's 'What It Means When a Man Falls from the Sky' for the interlinked stories. Lastly the stories in this project take from Sindiwe Magona's Mother to Mother for humanising bodies that have been reduced to frames.
Keywords: South African fiction (English) -- 21st century; African fiction (English) -- History and criticism; Short stories, South African (English) -- 21st century; Diaries -- Authorship